Estudos propagativos do coquinho-azedo (Butia capitata (Mart.)Becc) ARECACEAE - Rodrigo Carvalho Fernandes (2008)
Among the cerrado native fruits, coquinho-azedo (bitter coconut) (Butiacapitata) Becc. stands out for its socioeconomic importance, mainly to theneedy communities in the North of the state of Minas Gerais, Brazil. This fruit plays an important role as food source and income generation. However, factors as the intensive fruit extractivism, agriculture expansion and species propagation problems associated to the lack of scientific studies, has limited its use endangering its survival. This present study aims to evaluate aspects associated to the Butia capitata (Mart.) Becc. seeds physiological potential, in order to provide information to the sustainable use of the species. The two first studies evaluated the endocarp influence on the seed water absorption and the inhibitor substance presence in the seed germination and in different parts of the coquinho-azedo fruit. The other two studies aimed to characterize the embryonary development and to evaluate the viability of the seedsthrough the tetrazolium test, besides testing methods for surpassingdormancy of the coquinho-azedo seeds. In the first experiment, it wasobserved that the endocarp limits the water absorption by the seeds. In the second experiment, only the dry matter of the species seedlings wasnegatively affected by the fruit parts and the seed, especially the endocarp, exocarp and the seeds. The third study verified that the embryo extraction and the imbibition in tetrazolium solution (0,5%) for 4 hours with the absence of light turned to be the best method for visualizing the tissue color. Still in this work, it was observed that from 180 days after planting, the seeds with endocarp showed more viability than seeds without endocarp and that the embyos length showed crescent linear behavior in relation to different evaluated periods. In the fourth experiment, the endocarp removal provided higher germination indices (7.2%) and germination velocity (0.048%). Thus, the endocarp removal is the recommended pre-germination treatment to speed and standardize the coquinho-azedo germinative process.